Sector perception of circular economy driver interrelationships - Gue, Ivan Henderson V. (Animo Repository, 2020)
The shift to a circular economy requires careful planning, the first step of which is to understand the drivers of the transition. There have been few papers in the literature that have analyzed and mapped interrelationships of these transition drivers from the perspective of different sectors. This work presents a methodological framework for mapping causality networks for macro-level transition towards circular economy based on sector perceptions. Fuzzy DEMATEL is used to allow linguistic inputs to be quantified. This procedure allows drivers to be characterized as causes or effects based on their position in the causality network. A case study presents the Philippines as a representative developing country for circular economy transition. The inputs of seventeen respondents from retail and trade, manufacturing, construction, water services, food services, electricity services, academic services, and health services were elicited through a survey. These responses were then aggregated into the industry and service sectors. The drivers considered were government support, company culture, consumer demand, social recognition, economic attractiveness, and information to practitioners. Results show that economic attractiveness and consumer demand are unanimously seen as the causal drivers. All sectors identify company culture as an effect driver. The findings also indicate varying perceptions among sectors. Although these findings apply specifically to the Philippines, this methodology itself can be used for mapping driver interrelationships of other countries and regions. © 2020 Elsevier Ltd